Структурний аналіз проектів технологічних систем збирання врожаю - Сидорчук, Олександр Васильович; Пукас, Віталій Леонідович; Луб, Павло Миронович; Шарибура, Андрій Остапович (НТУ "ХПІ", 2018)
Виконано структурний аналіз проектів технологічних систем збирання врожаю сільськогосподарських культур. На підставі системного підходу означено укрупнені складові проектів технологічних систем збирання цукрових буряків. Наведено завдання щодо розкриття взаємозв‟язків між ними для розроблення відповідних методів і моделей дослідження (моделювання) проектів цих технологічних систем. Означено практичну цінність таких методів та моделей для вирішення завдань із обґрунтування раціональних параметрів технічного оснащення відповідних проектів.

The peculiarities of technological systems projects of agrarian production (crops harvesting) are outlined. There proven that the systematic approach need take into account the interaction of their components. The basic notions of material production are given. Those methodological peculiarities of projects management processes researching (modeling) of the technological systems in different branches of production, in particular for the sugar beets harvesting, are outlined. The research stages of these technological systems projects with the use of statistical simulation methods of corresponding projects are indicated. The consolidated components of sugar beet harvesting projects are singled out and their influence on the dynamics of these projects execution is conceptually disclosed. The project environment of sugar beet harvesting technological systems, as well as its influence on the works in these projects, has been characterized. The interaction peculiarities of the subject (sugar beet and field characteristics) and agro-meteorological conditions on the project execution possibility are outlined. It is proved that in order to objectively substantiate the parameters of the technical equipment of sugar beet harvesting projects it is necessary to develop methods and models that take into account the specifics of the influence of the project environment. The system links between hierarchical tasks of strategic, tactical and operational planning in projects of sugar beet harvesting technological systems are indicated. The solution of these tasks involves a clear sequence of research, which involving the simulation techniques for relevant projects. It has been established that disclosure of these interconnections plays a fundamental role in the formation of initial information and the development of appropriate methods and models for studying (modeling) projects of technological harvesting systems, as well as providing an opportunity to substantiate the rational parameters of their technical equipment.
Structural analysis of harvesting technological systems projects
Keywords: управління; середовище; моделювання; технічне оснащення; ТС; виробничий процес; environment; technical equipment